Pengaruh Medan Listrik Luar Terhadap Sudut Putar Polarisasi Sinar Laser Pada Gliserin - Perwirawati, Linda (JURNAL SAINS DAN MATEMATIKA, 2007)
ABSTRACT ---Nonlinear optical properties of glycerin solution with various concentration in the external electrics field has been studied. Optical properties studied here is rotation of direction electrics fields from red diode laser ray which transmition because external electrics field at sucrose and glycerin solution. The result of the experiment shows that change of linear polarization angle proportional to external electrics field and concentration. The change of linear polarization angle of sucrose solution is greater than glycerin solution, The applied small parallel plates show that change of linear polarization angle of light is more optimal than in big parallel plates. Keywords : external electrics field, non-linear optics, polarization, polarization angle